2011
DOI: 10.1016/j.ijpara.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Methionine transport in the malaria parasite Plasmodium falciparum

Abstract: The intraerythrocytic malaria parasite, Plasmodium falciparum, derives amino acids from the digestion of host cell haemoglobin. However, it also takes up amino acids from the extracellular medium. Isoleucine is absent from adult human haemoglobin and an exogenous source of isoleucine is essential for parasite growth. An extracellular source of methionine is also important for the normal growth of at least some parasite strains. In this study we have characterised the uptake of methionine by P. falciparum-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 36 publications
1
34
0
2
Order By: Relevance
“…The single predicted AAAP in P. falciparum (TransportDB; Figure 2) reflects the parasite's ability to internalize and digest haemoglobin from the host (Wunderlich et al, 2012), a valuable source of amino acids. However, haemoglobin is absent in isoleucine and low in methionine, which likely explains why the parasite imports these amino acids (Cobbold et al, 2011), although the transporter(s) responsible has not yet been identified.…”
Section: Parasite Amino Acid Transporters—the Aaap Familymentioning
confidence: 99%
“…The single predicted AAAP in P. falciparum (TransportDB; Figure 2) reflects the parasite's ability to internalize and digest haemoglobin from the host (Wunderlich et al, 2012), a valuable source of amino acids. However, haemoglobin is absent in isoleucine and low in methionine, which likely explains why the parasite imports these amino acids (Cobbold et al, 2011), although the transporter(s) responsible has not yet been identified.…”
Section: Parasite Amino Acid Transporters—the Aaap Familymentioning
confidence: 99%
“…In addition, parasites require purine precursors and pantothenate from the plasma56. While many of these metabolites can be transported across the erythrocyte plasma membrane and be subsequently utilized by intracellular parasite stages, others are either not transported or transported at a rate that is insufficient to sustain rapid parasite growth578910. The malaria parasite overcomes this problem by remodelling nutrient transport pathways in the erythrocyte membrane through the expression of the new permeability pathways (NPPs), which allow entry of a wide range of nutrients required for parasite growth, allowing faster permeation of smaller, anionic and non-polar solutes1112.…”
mentioning
confidence: 99%
“…The infected erythrocytes were cultivated either under "shaking" conditions, in RPMI 1640 medium (PAA E15-840; supplemented with 0.5% wt/vol AlbuMax II (Invitrogen), 25mM HEPES (N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid), 20mM glucose, 24 g/mL gentamicin and 200M hypoxanthine) at a hematocrit of 2%, 31 or under "static" conditions in the same medium supplemented with 10% vol/vol human serum (from the Marburg Blood Bank). 32 Experiments were carried out with trophozoitestage P falciparum-infected erythrocytes (30-35 hours after invasion) enriched to 85%-95% parasitemia either using a VarioMACS separation unit (Miltenyi Biotec) as described elsewhere, 6 or using the plasmagel method. 33 …”
Section: Cell Culturementioning
confidence: 99%
“…The estimation of the amount of radiolabel trapped in the extracellular space of the cell pellet, and the calculation of the distribution ratio, was performed as described elsewhere. 6 …”
Section: Amino Acid Uptake Measurementsmentioning
confidence: 99%
See 1 more Smart Citation